2006
DOI: 10.1073/pnas.0608159103
|View full text |Cite
|
Sign up to set email alerts
|

Independent and simultaneous translocation of two substrates by a nucleotide sugar transporter

Abstract: Nucleotide sugar transporters play an essential role in protein and lipid glycosylation, and mutations can result in developmental phenotypes. We have characterized a transporter of UDP-N-acetylglucosamine and UDP-N-acetylgalactosamine encoded by the Caenorhabditis elegans gene C03H5.2. Surprisingly, translocation of these substrates occurs in an independent and simultaneous manner that is neither a competitive nor a symport transport. Incubations of Golgi apparatus vesicles of Saccharomyces cerevisiae express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
3
31
1
Order By: Relevance
“…5A). This result resembles the one previously described for transporter CO3H5.2 and suggests that transporter SRF-3, which is closely related to transporter CO3H5.2 in the phylogenetic tree, is also closely related in the manner by which it transports substrates, namely a non-competitive, independent, and simultaneous manner (11).…”
Section: C03h52 Rnai Inactivation Is Consistent With E2797 Mutants Dsupporting
confidence: 72%
See 3 more Smart Citations
“…5A). This result resembles the one previously described for transporter CO3H5.2 and suggests that transporter SRF-3, which is closely related to transporter CO3H5.2 in the phylogenetic tree, is also closely related in the manner by which it transports substrates, namely a non-competitive, independent, and simultaneous manner (11).…”
Section: C03h52 Rnai Inactivation Is Consistent With E2797 Mutants Dsupporting
confidence: 72%
“…Very recently, a new nucleotide sugar multisubstrate transporter from C. elegans was characterized, CO3H5.2, with a novel, simultaneous, and non-competitive transport mechanism (11). We have now demonstrated that SRF-3, another C. elegans multisubstrate transporter, has a translocation mechanism that is similar to the one described for C03H5.2 and different from the one previously shown for SQV-7 (10).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Because mouse ES cells are male and hemizygous for Cosmc, we could use these cells to examine the consequences of complete Cosmc loss on protein glycosylation. The complex biosynthesis of glycoproteins requires the activities of many dozens of enzymes in the ER, Golgi, and other organelles in the secretory pathway, including nucleotide sugar transporters, glycosidases, glycosyltransferases, and other chaperones involved in glycoprotein assembly and movement to the cell surface (22)(23)(24)(25)(26). We found that although mouse ES cells with a null Cosmc lack T-synthase activity and express Tn antigen, all other protein glycosylation, including total N-glycan profiles by mass spectrometry, and cell growth appeared normal in vitro.…”
Section: Discussionmentioning
confidence: 99%